Express 2/y2-1 in partial fractions. Hence solve the differential equation 2xdy/dx +1 = y2 given that y= -3 when x= 1, expressing y explicitly in terms of x.
It follows that "\\frac{2}{y^2-1}=\\frac{1}{y-1}-\\frac{1}{y+1}" is the expression in partial fractions.
Let us solve the differential equation "\\frac{2xdy}{dx} +1 = y^2," given that "y= -3" when "x= 1." This equation is equvalent to the equation "\\frac{2xdy}{dx} = y^2-1," and hencev "\\frac{2dy}{y^2-1} = \\frac{dx}x." It follows that "\\int\\frac{2dy}{y^2-1} = \\int\\frac{dx}x," and hence "\\int(\\frac{1}{y-1}-\\frac{1}{y+1})dy= \\ln|x|+\\ln|C|." We conclude that "\\ln|y-1|-\\ln|y+1|=\\ln|Cx|," that is "\\ln|\\frac{y-1}{y+1}|=\\ln|Cx|," and hence "\\frac{y-1}{y+1}=Cx." Taking into account that "y= -3" when "x= 1," we conclude that "C=\\frac{-3-1}{-3+1}=2."
It follows that "y-1=2xy+2x," and hence "y-2xy=2x+1." Consequently, "y=\\frac{2x+1}{1-2x}" is the solution of the differential equation.
Comments
Leave a comment